ANALISIS PERSEPSI KONSUMEN TERHADAP EKUITAS MEREK PRODUK ES KRIM - Fitrahdini, Fitrahdini; Sumarwan, Ujang; Nurmalina, Rita (Jurnal Ilmu Keluarga dan Konsumen, 2010)
The brand equity is created not only by some dimensions of brand equity such as brand awareness, brand association, perceived quality, and brand loyalty but also created by marketing activities called antecedents of brand equity. This research used brand equity dimensions as variables. The aim of this research was to analyze consumer’s perceive toward brand equity of ice cream (IM Meiji). The data was collected from 150 respondents in Bogor. The data analysis technique was the multicolinearity measurement with Structural Equation Modeling (SEM) assisted by a computer application LISREL (Linear Structural Relationship) 8.3 version. The output analysis of SEM indicated that the structural model could be accepted (close-fit) based on empirical facts. The structural model indicated that the brand equity of ice cream products (IM Meiji) was created by brand association (compound with brand awareness), brand loyalty, and perceived quality. Brand loyalty with significant positive correlation toward brand equity had the biggest contribution, while the perceived quality had the lowest contribution with negative correlation toward brand equity. The estimation of parameter also showed that advertisement and distribution intensity had significant positive correlation towards brand equity, but price had negative correlation.